2012
DOI: 10.1007/128_2012_341
|View full text |Cite
|
Sign up to set email alerts
|

Natural-Agent Mechanisms and Early-Phase Clinical Development

Abstract: The evolution of chemoprevention research continues in exciting new directions. Large chemoprevention trials in unselected patients have often been negative, but this trend promises to be reversed by more-focused and novel trial designs emphasizing the identification of molecular targets and predictive biomarkers. Phase 0 designs, blood and tissue-based biomarkers, and surrogate endpoints are examples of important features of new prevention-trial design. Breakthroughs in the identification of novel mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Notably, myo -inositol, a natural sugar alcohol, enhanced regression of low-grade dysplasias in a phase I clinical trial [87]. Although myo -inositol can affect multiple signaling pathways [106], in the phase I trial, regression was accompanied with PI3K pathway inhibition [74,88], which our data support as being part of the mechanism of regression. Thus, natural and targeted PI3K inhibitors should continue to be investigated.…”
Section: Discussionmentioning
confidence: 51%
“…Notably, myo -inositol, a natural sugar alcohol, enhanced regression of low-grade dysplasias in a phase I clinical trial [87]. Although myo -inositol can affect multiple signaling pathways [106], in the phase I trial, regression was accompanied with PI3K pathway inhibition [74,88], which our data support as being part of the mechanism of regression. Thus, natural and targeted PI3K inhibitors should continue to be investigated.…”
Section: Discussionmentioning
confidence: 51%
“…This leads to the induction of pleural fibrosis that might result in cancer transformation [ 11 ] [ 12 ]. Within the last five decades, the natural products have continuously contributed to drug discovery and development process [ 13 ] [ 14 ] [ 15 ]. Increasing evidences have shown that natural products, including extracts and isolated chemicals, are multi-targeted and can be considered as a model to approach chronic diseases such as cancer.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Some botanical extracts, such as green tea extract, contain polyphenols that can modulate growth hormone/IGF signaling pathways and exhibit anticancer properties. 36 Certain plant compounds, including flavonoids and polyphenols from sources like cruciferous vegetables and berries, have demonstrated the potential to interfere with thyroid hormone signaling and inhibit thyroid cancer growth. 37 While targeted therapies specifically derived from plants against prolactin signaling in cancer are limited, further research to explore natural compounds with potential anti-prolactin effects is greatly needed.…”
Section: Disruption Of Hormonal Signaling Pathwaysmentioning
confidence: 99%